2023
DOI: 10.1021/acscatal.3c00548
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Structures and Catalytic Properties of Supported Bimetallic PtSn Catalysts for Propane Dehydrogenation Reaction

Abstract: Heterogeneous bimetallic catalysts are widely used in industrial processes, and the structural features of the bimetallic catalysts have profound impacts on their properties in numerous catalytic processes. Bimetallic nanoclusters with particle sizes ≤1 nm have shown better performances in various catalytic reactions in comparison to conventional bimetallic nanoparticles with sizes above 1 nm. Despite the progress made in recent years in the synthesis and catalytic studies of bimetallic nanoclusters, achieving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…However, as shown in Figure b, when the thermal treatment temperature reduced to 400 °C or increased to 700 °C, the diffraction peaks of Pt and Pt 3 Sn appear in Pt-Sn/Al 2 O 3 -400 and Pt-Sn/Al 2 O 3 -700, respectively. As shown in Figure S3 of the catalyst’s XPS results, no peaks attributed to zerovalent Sn were observed, which may be due to the small size of the Pt-Sn alloy nanoparticles …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, as shown in Figure b, when the thermal treatment temperature reduced to 400 °C or increased to 700 °C, the diffraction peaks of Pt and Pt 3 Sn appear in Pt-Sn/Al 2 O 3 -400 and Pt-Sn/Al 2 O 3 -700, respectively. As shown in Figure S3 of the catalyst’s XPS results, no peaks attributed to zerovalent Sn were observed, which may be due to the small size of the Pt-Sn alloy nanoparticles …”
Section: Resultsmentioning
confidence: 98%
“…The XANES spectra of the three Pt-Sn/Al 2 O 3 catalysts were similar to Pt-foil’s, which indicates that Pt present on Al 2 O 3 was in the metallic state. The relative electron density in the Pt 5d orbitals can be evaluated from the peak area of the white line in the XANES spectra, where a decrease in the peak area indicates an increase in the electron density of the Pt 5d orbitals. , An apparent shift in the white line peak position can be observed in Figure a, indicating the electron transfer from Sn to Pt during the formation of Pt-Sn alloy particles. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The PtSn@MFI catalysts with medium Pt loadings (0.02–0.14 wt %) comprise small PtSn clusters (with sizes of 0.4–0.6 nm), which exhibit superior performances for PDH because of their higher capabilities for C–H activation. However, the formation of large PtSn particles (>0.6 nm) will be less efficient for PDH as indicated by the low activities observed with samples of high Pt loadings (44PtSn@MFI and 58PtSn@MFI), which could be ascribed to the less amount of highly under-coordinated Pt sites in the large Pt particles …”
Section: Resultsmentioning
confidence: 99%
“…The advantages of substituting bimetallic nanoparticles with subnanometer bimetallic clusters have been demonstrated in prior studies, but it is quite challenging to clarify the optimal structural configurations of the tiny bimetallic entities. Though size-selected bimetallic clusters generated by physical methods can be employed as model systems of bimetallic catalysts, , comparative studies with practical solid catalysts with high structural uniformity and stability synthesized by chemical approaches can minimize the materials gap, which is beneficial for providing insights with high reference values. However, this approach is limited by the challenges in the controllable generation of subnanometer bimetallic clusters with well-defined structures and the difficulty in resolving the composition and surrounding environment of the subnanometer bimetallic active sites with atomic precision.…”
Section: Introductionmentioning
confidence: 99%
“…Although PDH is considered a structureinsensitive reaction, these side reactions exhibit a structure sensitivity. 7,8 It has been demonstrated that larger ensembles of active sites tend to catalyze these side reactions, including cracking and over-dehydrogenation. 9,10 Recently, the isolation of an active site has been proved to be an effective approach to address these challenges.…”
mentioning
confidence: 99%